Impact and effectiveness of a conjugate vaccine against invasive pneumococcal disease in Finland-a modelling approach - Rinta-Kokko Hanna; Nurhonen Markku; Auranen Kari (TAYLOR & FRANCIS INC, 2022)
The evaluation of the public health impact of a vaccination program is essential in monitoring its policy relevance. Vaccine impact (VI) is usually assessed in a before-after design, in which data on disease burden without vaccination program is required from a historical reference period. It takes into account the indirect effects and therefore aims to describe the public health performance of the vaccination program in the population. Vaccine effectiveness (VE), measured in parallel settings, quantifies the benefit for an individual of being vaccinated but does not address the indirect effects of a vaccination program. The motivation of this paper is to gain insight into patterns of how VI and VE have manifested under large-scale use of a ten-valent pneumococcal conjugate vaccine in Finnish children. We construct a simple pseudo-dynamic model that mimics typical post-vaccination trends in the incidences of pneumococcal carriage and invasive disease in children when the proportion of vaccine-type carriage decreases. In the context of the model, we define the parameters of interest for VI and VE and explore how their expected values evolve over time. For comparison, we demonstrate the application of VI and VE estimation by using register data.